Marketing approach to innovation management as a tool for enhancing innovative activity of enterprises - Bersimbayeva, A.B.; Uruzbayeva, N.A.; Aibossynova , D.A. (BUKETOV BUSINESS REVIEW, 2017)
First of all, for creating competitive advantages of Kazakhstan enterprises in markets with high competition it is necessary to rethink the scope and role of marketing in management the innovative activity of enterprises. However, in the Kazakh literature there aren’t any special studies devoted to the use of marketing in innovation management. As a consequence, the main purpose of this study is to present the importance of using marketing approach in management of innovative activity of enterprises as an effective tool to improve their innovation activity. This paper analyzes the views of domestic and foreign scientists on the role of marketing in the innovation process. On this basis, there is an expediency of using a marketing approach to the management of innovation performance of enterprises. The methodology of the study bases on the hypothesis about the necessity of consideration the category of «management of innovative activity» from the standpoint of an integrated approach – from the point of view of the manufacturer and from the point of view of the consumer. Features of this methodology are explained, on the one hand, the complexity of the phenomenon of innovation, the results of which may not always be appreciated by the consumer because of the lack of special knowledge and competencies, as well as the complexity of managing the process, on the other hand. The logical conclusion of the work proposed by the authors is the main uses of the marketing concept to improve the innovation activity of enterprises.